2013
DOI: 10.1007/s00787-013-0481-z
|View full text |Cite
|
Sign up to set email alerts
|

Anhedonia and depressed mood in adolescence: course, stability, and reciprocal relation in the TRAILS study

Abstract: Adolescence is marked by increases in the incidence of major depression (MDD), a disorder recognized as one of the leading causes of disability. Anhedonia and depressed mood predict both onset and chronicity of major depression (MDD), but have never been studied together longitudinally in the general adolescent population. The present study examined (1) the course and the stability of anhedonia and depressed mood and (2) their cross-sectional and longitudinal relations during adolescence. The study cohort cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 54 publications
2
50
1
Order By: Relevance
“…Nevertheless, the scant published data available suggest that the experience of anhedonia is common in population samples of adolescents (Bennik, Nederhof, Ormel, & Oldehinkel, 2013; Sanchez-Garcia et al, 2014) and is associated with risk of psychopathology and substance use in general population samples (Audrain-McGovern et al, 2012; Thomas, 2011). If an adequately valid measure of anhedonia in a general population sample of adolescents could be identified, this tool could be applied in epidemiologic surveys on the nature, risk factors, and consequences of anhedonia in general population samples of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the scant published data available suggest that the experience of anhedonia is common in population samples of adolescents (Bennik, Nederhof, Ormel, & Oldehinkel, 2013; Sanchez-Garcia et al, 2014) and is associated with risk of psychopathology and substance use in general population samples (Audrain-McGovern et al, 2012; Thomas, 2011). If an adequately valid measure of anhedonia in a general population sample of adolescents could be identified, this tool could be applied in epidemiologic surveys on the nature, risk factors, and consequences of anhedonia in general population samples of adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The measure assesses physical anhedonia and hedonic capacity with content similar to those used in traditional adult measures (Chapman et al, 1976; Fawcett et al, 1983; Snaith et al, 1995). Thus, we also know very little about the emergence of anhedonia with only one published study (Bennik, Nederhof, Ormel, & Oldehinkel, 2014) explicitly examining this issue. However, the generalizability of this work is questionable as the authors relied on a single item from the Youth Self-Report.…”
Section: Developmental Extensions Of Pvsmentioning
confidence: 99%
“…Only one published study examined changes in anhedonia longitudinally in adolescence (Bennik et al, 2014). The authors found that the likelihood of endorsement of anhedonia decreased from age 11 to 19 across four assessments, suggesting that anhedonia normatively declines in this period.…”
Section: Longitudinal Changes In Pvs Functioningmentioning
confidence: 99%
“…Hence in Bennick et al; longitudinal cohort survey anhedonia and depressed mood were assessed in 2,230 adolescents aged 11-19 years. This acknowledges trajectories for both girls and boys, as anhedonia decreased from age 11 years onwards in both sexes, whereas depressed mood increased in girls from age 11 years onwards, but only at certain ages in boys such as 13.5, 16.5 and 19 years.…”
Section: 3: Psychological Factorsmentioning
confidence: 99%